Dining with a Good Conscience: Augustine's Conversion with regard to Eating and Drinking - Egmond, Bart van (Augustiniana, 2025)
This article discusses the development of Augustine’s ethical convictions with regard to the consumption of food and drink. The first part of the article analyses the formation of Augustine’s ‘alimentary conscience’ during the years he was a Manichaean auditor. The second part delineates how his return to Catholic Christianity might have changed his views on eating and drinking. The third part gives a summary of Augustine’s final position.